Evaluation and optimization of wavelet technique to enhance the mapping accuracy of lightning VHF interferometry - Al-Ammari, Ammar Mohammed Qaid (2022)
Despite the significant progress in the understanding of the phenomenon of lightning and the physics behind it, locating and mapping its occurrence remain a challenge. Such localization and mapping of very high frequency (VHF) lightning radiation sources provide a foundation for the subsequent research on predicting lightning, saving lives, and protecting valuable assets. A major technical challenge in attempting to map the sources of lightning is mapping accuracy. Several methods have been proposed for estimating the real pattern of the temporal location and spatial map of the lightning strikes. However, due to the complexity of lightning signals and the noise accompanying its recording, providing accurate lightning maps estimation remains a challenging task. To advance the lightning mapping it is vital to improve how lightning signals are pre-processed and how noise is filtered. Most existing studies of lightning mapping make use of the VHF interferometer (ITF) alongside crosscorrelation in time and frequency domain and phase difference of arrival techniques. These methods involve selecting a set of parameters which usually fail to accommodate all types of lightning flashes, discarding information that could be beneficial for further improvement of lightning mapping accuracy. In this thesis, a wavelet-based cross-correlation (CCWD) is proposed for a reliable lightning mapping estimation through means of signal enhancement and noise reduction, providing a better time- frequency resolution. Interpolation techniques were introduced to smoothen the correlation peaks for more accurate lightning localization. To confirm the effectiveness of the proposed method, a simulation of lightning signals was created, and the mapping results were verified. Moreover, a comparative study to investigate the effectiveness of different processing techniques was carried out. The benchmark environment involved the use of different filtering and cross-correlation techniques, introducing new processing methods such as Kalman filter and wavelet-based crosscorrelation. In addition, a particle swarm optimization technique is used to optimize the trajectory of the CCWD-based lightning maps by finding the optimal sliding window of the cross-correlation. The CCWD-PSO technique was further enhanced through the introduction of a novel lightning event extraction method that enables faster processing of the lightning mapping. Six positive narrow bipolar events were analyzed, and the results indicate that a good estimation of the lightning radiation sources was achieved using wavelet de-noising and CCWD with a minimal error of 3.46°. The results were further improved with the use of CCWD-PSO technique with Euclidean distance of 0.6243 at 300 iterations. The investigations carried out in this study confirm that the ITF mapping system could effectively map the lightning VHF radiation source, which makes the combination of ITF and the CCWD a potential candidate for lightning mapping technology.